Hazard Analysis Critical Control Point (HACCP) analysis in the process of making moringa leaf sponge cake in X Hospital - pratiwi, niken (Politeknik Kementerian Kesehatan Banjarmasin, 2023)
Making moringa leaf cakes as a snack for cancer patients is one of the efforts to fulfill nutritional adequacy as well as a snack that has a complete composition. Processing with good and maximum quality control, so that contamination of raw materials into food can be controlled and can meet quality assurance based on HACCP. Moringa leaf sponge has potential biological, physical and chemical hazards. The analysis was carried out including direct observation and interviews with officers making Moringa leaf cakes. The type of research used is descriptive with a qualitative approach. The research was carried out at X Hospital Jakarta, in November 2022 with the object of research being an analysis of the application of HACCP in the process of making Moringa leaf cakes at X Hospital Jakarta. The results of the HACCP analysis obtained critical points from receiving raw materials to product packaging that can be controlled. Egg raw materials are washed with 50 ppm chlorine for 2-3 minutes after receipt, SNI standard wheat flour, moringa leaf powder, refined sugar, SNI standard cooking oil, and margarine with good storage to avoid the potential danger of lipolytic microbes. In the making of Moringa leaf cakes, there is a potential for contamination in the packaging process after the processing process. Proper use of PPE and the serving process affect the potential hazard of Moringa leaf cakes. This activity resulted in the finding that there is a potential hazard in the production of Moringa leaf sponge cake during the serving process.